Investigation of human arm musculoskeletal model using aluminium pole in palm oil harvesting process - Aliff, Rahman; Shahrol, Mohamaddan; Noor Aliah, Abdul Majid; Magdalene, Andrew Munot; Mahsuri, Yusuf; David Chua, Sing Ngie; Baba, Md Deros (IEEE, 2017)
Palm oil industry is one of the important sectors in Malaysia. The growth and development in this industry shows that Malaysia is one of the largest manufactures of palm oil in the world. However this industry does causing a lot of issues in Work-related Musculoskeletal Disorders (WMSDs) especially in Harvesting Process. In addition, some of the palm oil workers in Malaysia do not take serious consideration in ergonomics awareness for their safety and health. Most of the workers are still using manual tools such as aluminium pole which has a high potential to expose to the ergonomics risk factors. Upon that situation, these studies are focusing to identify the force reaction of arm muscle and the muscle activity throughout the movement of the worker using aluminium pole in palm oil harvesting process. Inverse Dynamic Analysis is used to investigate the modelled simulation.